MODELACIóN NUMÉRICA DE LA CIRCULACIÓN MARINA EN LAS BAHÍAS CALLAO y MIRAFLORES - Centeno y Cols., Mirian (2019)
The present work is related to study the surface circulation in Callao and Miraflores bays using Princeton Ocean Model (POM) model, which is a set of equations and parameters that govern the ocean dynamics. POM was used to caracterize the circulation pattern in the study area, analyzing the main influence of wind stress and tide in the generation of currents and the effects occur because of the coastal morphology and the presence of the Island, these factors influence the results indicating a complexity in the ocean currents and the presence of vortices inside the bay of Callao, also tidal propagation manifests in the area of the port of Callao, generating currents ebb and flow. In this way, knowing the ocean circulation in the Callao and Miraflores bays, further studies can be made pollutant dispersion, wastewater discharges, accidental spills of substances, and also sediment transport studies produced by the presence of Rimac and Chillon rivers.